Risk communication and trust in decision-maker action: a case study of the Giant Mine Remediation Plan - Cynthia G. Jardine; Laura Banfield; S. Michelle Driedger; Christopher M. Furgal (International Journal of Circumpolar Health, 2013)
Background. The development and implementation of a remediation plan for the residual arsenic trioxide stored at the former Giant Mine site in the Canadian Northwest Territories has raised important issues related to trust. Social and individual trust of those responsible for making decisions on risks is critically important in community judgements on risk and the acceptability of risk management decisions. Trust is known to be affected by value similarity and confidence in past performance, which serve as interacting sources of cooperation in acting toward a common goal. Objective. To explore the elements of trust associated with the development and implementation of the Giant Mine Remediation Plan. Design. Semi-structured interviews were conducted with eight purposively selected key informants representing both various interested and affected parties and the two government proponents. Results. Five primary issues related to trust were identified by the participants: (1) a historical legacy of mistrust between the community (particularly Aboriginal peoples) and government; (2) barriers to building trust with the federal government; (3) limited community input and control over the decision-making process; (4) the conflicted and confounded role of the government agencies being both proponent and regulator, and the resulting need for independent oversight; and (5) distrust of the government to commit to the perpetual care required for the remediation option selected. Conclusions. The dual-mode model of trust and confidence was shown to be a useful framework for understanding the pivotal role of trust in the development of the Giant Mine Remediation Plan. Failure to recognize issues of trust based on value dissimilarity and lack of confidence based on past performance have resulted in a lack of cooperation characterized by delayed remediation and a prolonged and expensive consultation process. Government recognition of the importance of trust to these issues will hopefully improve future communication and public engagement endeavours.